Determinants of financing decisions to fund startups by venture capital firms in Kenya - Wambua, D. K. (Strathmore University, 2025)
Kenya’s startup ecosystem presents unique dynamics that distinguish it from those of more developed economies, warranting a tailored examination of venture capital determinants. The local ecosystem is shaped by specific needs such as access to scalable funding, sector-focused support (especially in technology and agribusiness), and strategic guidance suited to an emerging market. Unlike established markets, regulatory frameworks in Kenya are evolving, creating an environment where venture funding decisions must consider varying levels of compliance and market volatility. The growing presence of incubators and accelerators further shapes the investment climate by offering essential mentorship, networks, and early-stage funding, which are crucial to the survival and growth of Kenyan startups. These context-specific elements underscore the importance of a region-focused study on venture capital financing and address gaps in existing literature predominantly focused on developed markets. This study sought to address this gap by investigating the determinants of Kenyan venture capital firms’ financing decision for startups Kenya. The specific objectives of the research were to investigate the influence of internal organizational determinants, external determinants, and incubation on Kenyan venture capital firms’ decision to finance startups in Kenya. The study was anchored on the Theory of Equilibrium Credit Rationing. The positivism philosophy was adopted for this research, which was performed using the cross-sectional research design. The sample for the current study comprised of finance and operation managers of venture capital firms in Kenya. The population of the study comprised 50 venture capital firms listed on the East African Venture Capital Association (EAVCA). A census was selected. Primary data was collected using structured questionnaires through a drop and pick approach and analyzed using Statistical Package for Social Sciences (SPSS). The findings showed that internal organizational determinants had a significant positive regression coefficient, suggesting a positive effect on Kenyan venture capital firms’ decision to finance startups. The analysis also showed that external determinants had a significant positive coefficient, indicating the positive influence of external determinants on the decision by venture capital firms to finance startups. Moreover, the findings indicated that incubation had a significant positive regression coefficient, which suggests a positive effect. Based on the findings of this study, it is recommended that policy makers should consider formulating policies to improve the external determinants and support incubation of startups. It is also recommended that owners and managers should improve their internal organizational determinants in order to favorably position themselves among venture capitalists. Keywords: Venture capital, financing, startups, Kenya
Full - text thesis